(untitled) (Human Factors in Design, 2013)
NAVMETRO® is a spoken dialogue system that provides information and a guidance function to the people with visual disabilities on Trindade’s metro station, in Porto, Portugal. The system usability in addition to assure the quality dialogue for all costumers should ensure the success in the guidance on the desirable way in the metro station. This article presents the results of the preliminary assessment developed on NAVMETRO® and that represents an important stage of the usability assessment of this system.